Representation of Self Healing in the Song Lyrics "Self" by Muhammad Tulus Rusydi Rholand Barthes' Semiotic Analysis Study - Adelia; Fakhrur Rozi; Syahrul Abidin (International Journal of Cultural and Social Science, 2023)
This study discusses the meaning of the self-healing symbol contained in the lyrics of the song "Self" in the album Manusia by Muhammad Tulus Rusydi in Roland Barthes' semiotic perspective. The symbol of self-healing in the lyrics of the song "Self" in the album Manusia by Muhammad Tulus Rusydi in the semiotic perspective of Roland Barthes who explains how to analyze the meaning of signs. In the song "Self" represents the symbol of Self Healing, namely forgivness which discusses about making peace with the past, gratitude discusses appreciation of oneself, positive self talk discusses expressing gratitude to oneself, expressive writing and mindfulness which discusses efforts or methods in self-reflection.